ESTIMATING OFF –FARM LABOR SUPPLY AND ANALYSING RELATIONSHIP BETWEEN RISK AND FARM SIZE - Awf A. A.; E. H. Ali; A. S. Shukr (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to estimate off-farm labor supply model. Data were collected randomly from 267 wheat producers in Salah El-Din province for the year 2020, 67.4% of them are produced using pivot sprinklers for irrigation and with three tenure categories (60,80,12) dunums. Furthermore. The KS coefficient was used to analyze the producers’ risk-taking behavior after estimating the production function and determining the area variable that has the most influence on the production process. If it increased by 1%, production would increase by 0.802%. The farmer’s decision to adopt the technology was based on economic, social, and institutional factors. It turns out that 40% of farmers make their decision based on financing. When analyzing the decisions of farmers under risk, it was found that 35% of them make the decision in relation to the price, which is the main incentive for production. In order to understand the relationship between the risk, the return, and the size of the farm, it was found that when the area is increased, the return increases, and the revenue of a dunum at the tenure size of 10 dunams amounted to 481,600 dinars and at a higher KS level, what is known as risk-haters, the revenue was the highest possible and the risk also increased with it, and the farmers became among the large holdings they prefer. In any case, some farmers believe that when you want to get a higher return, it is important to keep in mind that there is a greater risk. Risk is affected by a number of factors, including economic, divided into price and productivity, social ones, and others related to the farmer himself in terms of efficiency, management, skill, and experience. . The research recommended a review of tenure laws and the development of risk management strategies by providing adequate funding that ensures ,Providing factories within rural areas that contribute to absorbing surplus production, creating price stability, as well as creating a labor market that reduces poverty in the rural area.